How do personal resources sustain career resilience under employment uncertainty? A conservation of resources perspective - Fairuzzabadi, Fairuzzabadi; Rahmawati, Syarifah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Purpose – This study examines how interdependent personal resource systems, human capital, social capital, positive psychological capital, and spiritual capital collectively sustain career resilience under conditions of persistent employment uncertainty, drawing on Conservation of Resources (COR) theory.Design/methodology/approach – This study employed a quantitative design, collecting survey data from 366 working professionals in a collectivist cultural setting and analyzing the data using partial least squares structural equation modeling (PLS-SEM). The study evaluates the relative and combined effects of multiple personal resources on career resilience.Findings – All four forms of personal resources positively contribute to career resilience, with positive psychological capital exerting the most substantial effect. The results demonstrate that career resilience is not driven by isolated resources but by coordinated resource portfolios that mitigate cumulative resource loss, consistent with COR theory’s resource investment and gain–loss dynamics.Research limitations/implications – The study relies on cross-sectional, convenience-based data, limiting causal inference and generalizability. Future research should adopt longitudinal designs and examine mediating and moderating mechanisms within personal resource systems to extend COR-based career resilience models.Practical implications – Organizations and policymakers should move beyond single-resource interventions and adopt integrated development strategies that simultaneously enhance psychological, relational, skill-based, and meaning-oriented resources to foster sustainable career resilience.Originality/value – This study enhances career resilience theory by applying COR theory in a career context, integrating spiritual capital into resilience research, and providing cross-cultural evidence that challenges individualist assumptions in dominant career models